A Study On Anaerobic Cellulolytic Bacteria Isolated From Ruminants - Frances Foong, Frances C.F. (1986)
The study of rumen micro biology began in the 1940s but the progress made from those years onwards have not been able to match the burgeoning studies in genetic engineering aimed at optimizing the process of cellulose digestion. The basic study of the complex bacteria l processes involved in cellulose digestion will provide a rational baseline which is important in such an undertaking . The need to develop simpler and more efficient methods of isolation, characterization, enumeration and maintenance of cellulolytic bacteria a real so important because this will provide new strains of organisms that will be very valuable in the determination of the molecular processes of cellulose digestion an d in the development of genetically engineered improvements. In view of this, a project was undertaken to improve the isolation method for cellulolytic bacteria and to study their adaptability and cellulolytic characteristics in vitro .